(untitled) (Fiep Bulletin - online, 2013)
The progress of studies about the therapeutic benefits that work in the aquatic environment can bring, has developed increasingly. The hydrotherapy will gain new perspectives and be singled out as one of the best programs of rehabilitation multi disciplinary. Although it appeared in antiquity, its prestige is recovered in the past decade since then has become the subject of studies, allowing the progress of its techniques and improved treatments and is an excellent point to support the work of rehabilitation. The change in the posture of the patient, his decubitus orthostatic, the redistribution of blood volume, changes in the flows and pressures circulatory, are the main factors involved in this type of treatment. The effects depended on each patient, and also of immersion, which includes depth to the pool and the hydrostatic pressure. The purpose of this study was to present a proposal to adjust to the aquatic environment, to a patient of 28 years, who suffered spinal cord injury level T12-L1, examining the period of twelve attendants, through measuring the scale of assessment FIM and used water in sector of hydrotherapy of Physical Therapy Clinic of the FAG Faculdade Assis Gurgacz, the influence of change of posture and immersion of the body in the water. His results were presented through graphics and simple percentage calculation, where the evolution of the scale FIM was 9%, 40% buoyancy in rotation and 75%. Thus, it can be said that this study, the program of adaptation to the water environment was favorable.